A report on the practice-in-industry training in fish preservation. - Bayot, Ruben G.
There is no record in history and no one knows when men first learned how to preserve food, but we can be certain that it must have been a thousand years ago. Early attempts were storing in caves and covering them with snow. This was only practiced during winter, and perhaps men learned how to smoke and dry fish when discovered how to make fire. The discovery of the machine and the influx of ideas from other countries lead us to our present method of preserving food.